(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
By a graph G = (V, E), we mean a limited undirected graph with neither circles nor various edges. The request and size of G are indicated by n = |V | and m = |E| separately. For graph theoretic phrasing we allude to Chartrand and Lesniak [7]. In Chapter 1, we gather some essential definitions and hypotheses on graphs which are required for the consequent parts. The separation d(u, v) between two vertices u and v of an associated graph G is the length of a briefest u-v way in G. There are a few separation related ideas and parameters, for example, unpredictability, range, distance across, convexity and metric measurement which have been explored by a few creators as far as theory and applications. A magnificent treatment of different separations and separation related parameters are given in Buckley and Harary [6]. Let G = (V, E) be a graph. Let v ∈ V. The open neighborhood N(v) of a vertex v is the arrangement of vertices adjoining v. Hence N(v) = w ∈ V : wv ∈ E. The shut neighborhood of a vertex v, is the set N[v] = N(v)